Vulvar carcinoma in young patients and its relationship with genital warts - Traiman, P. [UNESP]; Bacchi, C. E.; De Luca, L. A.; Uemura, G.; Nahás Neto, J.; Nahás, E. A.P.; Pontes, A. (My University, 1999)
We report the occurrence of aggressive vulval carcinoma associated with condyloma acuminata in three patients under 33 years old. Discussion of the role of the human papilloma virus (HPV) in the development of vulvar cancer is also presented. Three patients with condyloma associated with aggressive vulvar squamous cell carcinoma, in situ (1 case) and invasive (2 cases), documented by biopsy and/or vulvectomy are presented. In situ hybridization (ISH) was used to characterize the subtypes of HPV. One patient with erythematous systemic lupus developed in situ carcinoma after 5 years. The other two cases also developed aggressive multicentric, invasive squamous cell carcinoma after 10 years of diagnosis of condyloma. In all cases HPV cytological abnormalities were seen throughout the pathological examination. HPV 16 and 18 were present in cells of invasive squamous cell carcinoma in cases 2 and 3. HPV 6 and 11 were detected only in the condyloma area in case 2. HPV 30 was seen only in the condyloma area in case 3. This report emphasizes the need for biopsies of all unusually persistent or treatment-resistant condylomas, particularly in young and/or immunoisuppressed patients.
Keywords: Carcinoma; HPV, vulvar; In situ hybridization; Young patients